The greening of a local community dynamics in environmental care discourses in community learning - Arzadon, Maria Mercedes Estigoy (2006)
The paper explored the dynamics of environmental care discourse and identify them in the context of community learning in Barangay Bued. Ethnography was employed along with deconstruction and critical discourse analysis. Participant obvservation was also utilized. Four environmental care discourses were identified. The spiritual discourse views environmental care as a religious campaign. Techno-managerial discourse is about using the right processes and materials. Environmental area as an economic concern is about providing income to waste management workers and lucrative profit to owners of waste-related businesses. The communitarian discourse casts the people as culturally capable to work together to protect their environment. Ultimately, the study argued that greening of a local community is a synergy of Formal, Nonformal, and Informal Education.